PERFORMANCE ANALYSIS OF LiVO3-Ion BATTERY WITH CARBON (Ipomoea Aquatica) AS ANODES - Sucia, Arini; Haryati, Sri; Syarif, Nirwan (AUSTENIT, 2022)
This research was conducted by utilizing water spinach which is found in swampy areas as new material for support in battery. Water spinach stems were separated used as carbon precursor. The carbon was prepared through hydrothermal and pyrolysis processes.  The battery was constructed using the carbon anode  and cathode from  LiVO3. The LiVO3 was produced by using hydrothermal process of LiCl, V2O5, and NaOH in 200ºC 30 bar for 16 hours. The performance of the battery was evaluated using cyclic voltammetry and galvanostatic charging – discharging methods on potentiostat. The electrolyte used was LiCl in liquid or gel electrolyte with concentrations of 10%, 20% and 40%, respectively. The binders were used PU and melamine. Material characterization reveal that the carbon has crystaline phase, conductivity and pores which therefore carbon has the capability to be used as anode precursor. The evaluation of battery performance showed that the highest current value was found in battery with 40% LiCl of liquid electrolyte and  polyurethabe binder, that is 0.22 A. The highest power 5.36 x   W, energy 1.80 x  Wh, and capacity  ​8.94 x  F  was found in battery with 40% LiCl of liquid electrolyte with binder PU.. The lowest battery discharge slope 0.0039 was found in 40% LiCl of liquid electrolyte with PU binder. These findings provides an alternative to the use of materials in Lithium ion batteries without compromising the performance of their application.